Cyber defence in industry 4. 0 systems and related logistics and IT infrastructures - Dimitrov, Konstantin (NATO science for peace and security series. Sub-series D: Information and communication security, 2018)
Intro -- Title Page -- Preface -- Contents -- Chaos-Based Communication Schemes for Improved Security in 4G Networks -- Leveraging Knowledge Graph Embedding Techniques for Industry 4.0 Use Cases -- Risks and Advantages in Using Artificial Intelligence on Cyber Defence and Cyber Attack -- Cyber Platforms for Adaptive Cyber Defence in Industry 4.0 and Logistics Systems Based on Intelligent Fault Diagnosis -- Knowledge-Based Smart System Core for a Globally Connected Cyber-Physical System with Industrial Security Application -- Industry 4.0: Global Analysis of Energy Considerations and Cyber-Security Constraints -- Cyber-Risk Analysis and Security in Supply Chain Management Based on ICT Systems -- Cyberspace and Cyber Warfare -- Industry 4.0 Intelligence Under Attack: From Cognitive Hack to Data Poisoning -- Network Layer Attacks Against Cyber-Physical Systems and Mitigations -- Hardware Rooted Security in Industry 4.0 Systems -- Subject Index -- Author Index